PENGELOLAAN PERLENGKAPAN PERKANTORAN PADA KANTOR CAMAT PONTIANAK KOTA - Rian Fahlevi E.21110106 (FISIP Universitas Tanjungpura, 2012)
Abstract This research aims is identify and describe the simplification of planning and savingconsumables, conducted by the employees of Pontianak mayor Office. Research method forconducting this research was qualitative and the presentation done by descriptive. because theproblem available only break through with qualitative. To enhance the research result, Ichoose secretary of subdistrict and other informan whose work on sub district Pontianak Kota.The results showed that, before goods were be used it must initial with planning. Second, goodthat be used by officer dedicated for third base on the efficiency and effectiveness standard,office equipment that being used is still not efficienct yet. This can be seen from the use of itemsthat have not been classified according to the type and condition as warehouse storage doesnot exist.Therefore, management activities of office supplies need to be managed properly inorder to provide services based on the legality of the administration. Keywords: Management of equipment, office administration.